Estado atual do problema da poliomielite no município de São Paulo - Victório Barbosa (Revista de Saúde Pública, 1968)
Estudo do problema da poliomielite no município de São Paulo, desde 1933 até 1967, dando ênfase ao período de 1962 a 1967, quando é analisada a relação entre a variação da incidência da doença em tela e as campanhas de vacinação em massa com a vacina de vírus vivos atenuados, então relizadas. Com base nos dados apresentados, conclue-se que no ano de 1967, em que o coeficiente de morbidade por 100.000 habitantes por poliomielite foi de 0,6, foi possível se conseguir o controle dessa doença em nossa Capital. The problem of poliomyelitis in the county of São Paulo, Brazil, was studied from 1933 to 1967. It emphasizes the period of 1962 to 1967, when the author analizes the relation between the variation in the incidence of the disease and the mass vaccination campaigns with the live virus vaccine attenuated accomplished at that time. Based on the data presented he concludes that in 1967, when the morbidity rate by poliomyelitis was 0.6 for 100,000 inhabitantes, it was possible to get the control of that disease in the county of São Paulo.